Ecological Assessment of the Amazon Sailfin Catfish (Pterygoplichthys Pardalis) In the Langat River, Malaysia - Samat, Abdullah (2008)
This study identified the ecological characteristics of an exotic fish species, Pterygoplicthys pardalis that have successfully occupied Malaysian rivers. The objectives of the study were to investigate the existing environment of Langat River where this species were found which included the water quality, food availability and habitat types, and to understand the basic ecology of the fish species including feeding, growth, reproduction that have contributed to the successful colonisation. The prediction was if the existing environment is suitable for the species, then the survival of the species will be enhanced due to favorable growth and reproduction. The study was conducted in Langat River between January 2003 and December 2004, and seven sampling sites (S-1 to S-7) were established. Statistical inference was used to estimate certain parameters (physical and biological) that are important in hypothesis testing. The physicochemical parameters of the water except dissolved oxygen (< 5 mg/l), total suspended solid (> 400 mg/l), chemical oxygen demand (> 50 mg/l) and ammonia-nitrogen (> 0.2 mg/l) were within the tolerance levels to most indigenous fish species. In the existing environment, the P. pardalis showed a negative allometric growth dimension (b = 2.538 ± 0.039). The influence of seasonal rainfall (water level) on the condition of P. pardalis was not evident. Good structure and function of its digestive tract has enabled the consumption of many and various kinds of food materials. Small size food particles (< 500 μm) were preferred and detritus from sediment was its major diet composition. The percentage of the food items identified both in the stomach and on the river bottom was almost similar, indicating that this fish fed on the food available in the habitat. The reproductive performance of this species was based on the male-female ratio of 1:1.7 and continuously reproduced that peaked during the rainy season between September and January. The number of eggs (fecundity) varied from 1,297 to 18,791 per brood and they were asynchronic batch spawner. Eggs were deposited deep (about 1 m) in the burrow to hide them from predators. Pterygoplichthys pardalis is a hardy species and exhibited typical characteristics of an invasive species where it has successfully survived in the Langat River.